Cell Death Mechanisms Produced by Carbon-Based Nanoparticles - Santos-Adriana Martel-Estrada; Claudia-Lucía Vargas-Requena; Josue-Itan Sifuentes-Chavarría; Maileth-Yoelis Yepes-Mendoza; Daniel-Santiago Palacio-Castillo; Florinda Jimenez-Vega; Imelda Olivas-Armendáriz (Journal of Nanotechnology)
Using carbon-based nanoparticles, such as diamond, graphite, fullerene, and nanotubes, has increased their research as possible strategies for drug delivery to control diseases, especially cancer. However, because these materials, when interacting with the living environment, release substances that are capable of inducing cell death by themselves, it is of vital importance to analyze the type of cell death that the particle can induce. Although there are different efforts to describe the kind of nanoparticles used to treat diseases such as cancer, no paper explains the mechanisms of cell death induced by different nanoparticle systems. Therefore, this paper attempts to gain cutting-edge information on using carbon-based nanopolymorphisms and the mechanism of cell death that the particles produce. In conclusion, carbon nanoparticles can interact directly with cell membranes, causing physical damage and disturbing the integrity of the membrane. This alteration can mainly lead to cell death by necrosis or apoptosis. The definition of a predominant mechanism for each nanoparticle depends on a dose-dependent manner. Primarily, the concentrations used to analyze cytotoxicity were 100–500 μg/mL. In several studies analyzed, it was only possible to find that the nanodiamonds proved not to be cytotoxic.